From Planning to Implementation of the YouthCan IMPACT Project: a Formative Evaluation - Henderson, Joanna (J Behav Health Serv Res, 2019)
In order to improve the youth mental health system, there is an international movement toward developing community-based service hubs that provide integrated, collaborative care to youth. However, the implementation of multisystem collaboration is complex and can be hampered by barriers. This paper presents a formative evaluation of the YouthCan IMPACT integrated youth services project based on the Consolidated Framework for Implementation Research (CFIR), to identify facilitators and barriers to successful implementation. Results highlight that previous positive working relationships along with collaborative investment of resources from partnering organizations are essential to implement an integrated youth service model. In addition, it is important that representative members of all key stakeholder groups, including staff, youth, and caregivers, be involved in the development and execution of the project to ensure effective implementation. Attention to the facilitators and barriers to implementation may help teams seeking to implement highly collaborative, integrated models of service delivery for youth in the community.